Type and Abundance of Phytoplankton in Lubuk Larangan Area, Sungai Paku Village, Kampar District, Riau - Rama Wahyudi; Muhammad Fauzi; Eko Purwanto (Jurnal Perikanan dan Kelautan, 2026)
This study aims to determine the types and abundances of phytoplankton species in Lubuk Larangan, Desa Sungai Paku. This research was conducted in May-June 2024 in Lubuk Larangan, Sungai Paku Village, Kampar Kiri District, Kampar Regency. The method used was the survey method, and data analysis was conducted using statistical tests. Phytoplankton species found in Lubuk Larangan, Sungai Paku Village, were 33 species belonging to 5 classes: Chlorophyceae, Cyanophyceae, Diatome, Euglenophyceae, and Zygnematophyceae. The abundance of phytoplankton species ranged from 7.080 to 16.800 cells/L. The highest phytoplankton abundance was at station II (16.800 cells/L), and the lowest was at station I (7.080,8 cells/L). Diversity index values ranged from 3.2883 to 3.7419, uniformity index 0.90 to 0.95, and dominance index 0.08 to 0.11. The high abundance of phytoplankton species obtained in the lubuk larangan (Station II) compared to the area outside the lubuk larangan (Stations I and III) indicates a difference type and abundance of phytoplankton with the results of the T test obtained a significant value of 0.028 (p < 0.05) and the value of T count is 3.374 and the value of T table is 2.77645 where T count is greater than T table